Does the Brain-Derived Neurotrophic Factor Val66Met Polymorphism Modulate the Effects of Physical Activity and Exercise on Cognition?. (February 2022) - de las Heras, Bernat; Rodrigues, Lynden; Cristini, Jacopo; Weiss, Maxana; Prats-Puig, Anna; Roig, Marc
The Val66Met is a polymorphism of the brain-derived neurotrophic factor (BDNF) gene that encodes a substitution of a valine (Val) to methionine (Met) amino acid. Carrying this polymorphism reduces the activity-dependent secretion of the BDNF protein, which can potentially affect brain plasticity and cognition. We reviewed the biology of Val66Met and surveyed 26 studies (11, 417 participants) that examined the role of this polymorphism in moderating the cognitive response to physical activity (PA) and exercise. Nine observational studies confirmed a moderating effect of Val66Met on the cognitive response to PA but differences between Val and Met carriers were inconsistent and only significant in some cognitive domains. Only five interventional studies found a moderating effect of Val66Met on the cognitive response to exercise, which was also inconsistent in its direction. Two studies showed a superior cognitive response in Val carriers and three studies showed a better response in Met carriers. These results do not support a general and consistent effect of Val66Met in moderating the cognitive response to PA or exercise. Both Val and Met carriers can improve specific aspects of cognition by increasing PA and engaging in exercise. Causes for discrepancies among studies, effect moderators, and future directions are discussed.